2019
DOI: 10.3389/fgene.2019.01225
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Realized Selection Response on Fillet Yield in Rainbow Trout Oncorhynchus mykiss, Using Sib Selection or Based on Correlated Ultrasound Measurements

Abstract: Selection using sib information on rHGCW was on average more efficient than selection using the candidates' own E8/E23 phenotypes, and downward selection (decreasing Fillet%) was more efficient than upward selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Broodstock selection in fish has been based on somatic growth [ 5 ], feed efficiency [ 6 ], disease resistance [ 7 ], deformities [ 8 , 9 ], fillet yield [ 10 , 11 , 12 ] or fillet fatty acid composition [ 13 , 14 ]. Selective breeding programs in gilthead seabream have also addressed improved growth performance, disease resistance and carcass quality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Broodstock selection in fish has been based on somatic growth [ 5 ], feed efficiency [ 6 ], disease resistance [ 7 ], deformities [ 8 , 9 ], fillet yield [ 10 , 11 , 12 ] or fillet fatty acid composition [ 13 , 14 ]. Selective breeding programs in gilthead seabream have also addressed improved growth performance, disease resistance and carcass quality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In France, fish farms dedicated to this species represent the majority of aquaculture operations; their production has historically been diversified into multiple target sizes, with the pan-size (250–350 g), and moderately large (>1 kg) or very large (>2.5 kg) individuals. Most of animals are female, diploid or triploid, and reared for the production of fillets, which are consumed fresh or smoked ( Vandeputte et al, 2019 ). For both economic and environmental reasons, the main challenge in trout production is promoting efficient growth while maintaining the quality of the fillet.…”
Section: Introductionmentioning
confidence: 99%
“…The final step in improving trout breeding programmes is to incorporate knowledge of the genetic architecture underlying trait variation. To date, most previous studies aimed at elucidating the genetic parameters of growth-related and quality traits in rainbow trout have focused on traits of primary economic importance, such as carcass yield, fillet yield, fat content in muscle, and fillet colour ( Gjerde and Schaeffer, 1989 ; Haffray et al, 2012 , 2014 ; Lhorente et al, 2019 ; Hu et al, 2020 ); two such selection programmes reported realised genetic gain in the range of 0.5–1% for fat in the muscle ( Quillet et al, 2005 ) and carcass and fillet yields, as predicted by ultrasound technology ( Vandeputte et al, 2019 ). However, the genetic architecture of yield traits is still poorly understood, and almost no attention has been paid to quality traits such as flesh colour or fat distribution.…”
Section: Introductionmentioning
confidence: 99%
“…These poor accuracies are in line with the present results and relate to the fact that most of the variation observed in fillet weight is explained by the variation observed in fish weight. Vandeputte et al [ 31 ] had already pointed out fillet yield being mostly proportional to body weight as one of the main problems in selecting for increased fillet yield. Rutten et al [ 32 ], for instance (whose best model, using length, height, width and corrected length, only explained 15% of the variation observed in fillet yield), showed a correlation of 97% between body weight and fillet weight in Nile tilapia, resulting in a much smaller CV for fillet yield than for fillet weight or volume.…”
Section: Discussionmentioning
confidence: 99%